2019
DOI: 10.1155/2019/2121849
|View full text |Cite
|
Sign up to set email alerts
|

Mesangial Cells Exhibit Features of Antigen-Presenting Cells and Activate CD4+ T Cell Responses

Abstract: Background. Mesangial cells play a prominent role in the development of inflammatory diseases and autoimmune disorders of the kidney. Mesangial cells perform the essential functions of helping to ensure that the glomerular structure is stable and regulating capillary flow, and activated mesangial cells acquire proinflammatory activities. We investigated whether activated mesangial cells display immune properties and control the development of T cell immunity. Methods. Flow cytometry analysis was used to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Moreover, the activated cDCs with tRA pre-treatment may have directly contributed to the activation of mesangial cells in the kidney through producing an array of pro-inflammatory cytokines and chemokines (84)(85)(86)(87)(88). Recent findings by Yu et al (89) provide support for our explanation that the potentiation of mesangial cell activity by tRA pre-treatment contributes to exacerbation of pristane-induced glomerulonephritis. They found that in vitro-activated mesangial cells could act as nonprofessional antigen-presenting cells and express cell surface molecules associated with antigen presentation including MHC-II, ICAM-1, CD40, and CD80, and therefore were able to prime co-cultured T cells to promote their activation and polarization toward T helper-1 (Th1) cells (89).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, the activated cDCs with tRA pre-treatment may have directly contributed to the activation of mesangial cells in the kidney through producing an array of pro-inflammatory cytokines and chemokines (84)(85)(86)(87)(88). Recent findings by Yu et al (89) provide support for our explanation that the potentiation of mesangial cell activity by tRA pre-treatment contributes to exacerbation of pristane-induced glomerulonephritis. They found that in vitro-activated mesangial cells could act as nonprofessional antigen-presenting cells and express cell surface molecules associated with antigen presentation including MHC-II, ICAM-1, CD40, and CD80, and therefore were able to prime co-cultured T cells to promote their activation and polarization toward T helper-1 (Th1) cells (89).…”
Section: Discussionsupporting
confidence: 80%
“…Recent findings by Yu et al (89) provide support for our explanation that the potentiation of mesangial cell activity by tRA pre-treatment contributes to exacerbation of pristane-induced glomerulonephritis. They found that in vitro-activated mesangial cells could act as nonprofessional antigen-presenting cells and express cell surface molecules associated with antigen presentation including MHC-II, ICAM-1, CD40, and CD80, and therefore were able to prime co-cultured T cells to promote their activation and polarization toward T helper-1 (Th1) cells (89). It is likely that the combination of pristane and tRA pre-treatment creates a favorable cytokine/chemokine environment for mesangial cell proliferation, whereas the proliferating mesangial cells would acquire abilities to present antigens, thereby promoting Th1 differentiation and renal inflammation.…”
Section: Discussionsupporting
confidence: 80%
“…Once differentiated, Th17 cells secrete their cytokines (IL-17A, IL-17F, IL-17C, IL-21, and IL-22), most of them with a pathogenic role in the kidney (32, 86-88), in addition to its systemic effects (1,15). Regarding Th17 cells differentiation, it is also worth mentioning that podocytes, mesangial cells, and renal tubular epithelial cells can behave as antigen-presenting cells (89)(90)(91)(92). So, these intrinsic renal cells can alone trigger the local activation of Th17 cells after recognizing, processing, presenting eventual DAMPs that cross the glomerular filtration barrier, as seen in other kidney disease models (89,93,94).…”
Section: Activation and Differentiation Of Th17 Cellsmentioning
confidence: 99%
“…The multifunctional cytokine IL-10 is primarily produced by stimulated T cells and suppresses strong inflammatory reactions [ 35 , 36 ]. Marconi et al [ 37 ], in their research with human serum, demonstrated that, together with IL-4, it induced IgA production, which is in line with our studies.…”
Section: Discussionmentioning
confidence: 99%